Α Computational Fluid Dynamics and Experimental Investigation of a CT9 Turbocharger Compressor at Low Rotational Speeds - Anh, Pham Hoang; Ky, Le Hong (Engineering, Technology & Applied Science Research, 2026)
This study provides the first validated Computational Fluid Dynamics (CFD)-experimental dataset for the CT9 compressor in the low-speed range of 10,000-20,000 rpm. Steady-state compressible Reynolds-Averaged Navier–Stokes (RANS) simulations were performed using the SST k–ω turbulence model following a verified mesh independence study. Pressure ratio and temperature rise measurements were obtained using a controlled gas stand test facility. The numerical results show strong agreement with the experimental pressure ratio data, the deviations in the isentropic efficiency are primarily due to mechanical losses and thermal effects. The results establish a reliable performance benchmark and improve the understanding of compressor behavior under turbo-lag-related operating conditions.